THE IMPLEMENTATION OF PROCEDURAL LAW OF RESPONSIBILITY ENFORCEMENT OF CORPORATE CRIME IN INTEGRATED CRIMINAL JUSTICE SYSTEM - Timbo Mangaranap Sirait (Jurnal Dinamika Hukum, 2017)
Privatization of business in various countries greatly affects on economic growth and development that corporate’s activities increasingly dominate legal subjects of Person and State. It also tends to trigger corporate crime. The issues of this research are causes of ineffective criminal procedural law implementation, how to anticipate those causes to create impartial judiciary, and how to reform corporate criminal procedural law “ius constituendum” that is holistic in order to create equal formulation between Person and Corporation. Then, it can be concluded that, First, corporate criminal procedural law “Ius Constitutum” is still centralized and fragmented, Second, a systematic and integrated corporate criminal procedural law is required, Third holistic reformation policy of corporate criminal procedural law “ius constituendum” which hierarchically equals to Law must be immediately formulated. Therefore, it is recommended to be discussed and legalized in Prolegnas 2018. Keywords: Corporation, Enforcement, Criminal Procedural Law, Integrated